Serially concatenated continuous phase modulation with iterative decoding. - Moqvist, P.
Serially concatenated and interleaved continuous phase modulation (CPM) with iterative decoding is investigated. An a posteriori probability (APP) algorithm for CPM is developed based on the classic APP algorithm for channel codes. The system is analyzed through upper bounds on the average bit error probability. For coded and interleaved minimum shift keying, the weight spectrum is computed, resulting in a transfer function bound. This is cumbersome for a general CPM system; instead, only the most significant error events contributing to the weight spectrum are identified. Simulations show that, firstly, these events give a satisfactory view of system performance when equal outer codes are used, and secondly, that remarkably good performance can be obtained for some simple systems. Finally, power spectral densities and bandwidths are computed, allowing for a bandwidth/performanee comparison of different combinations
Keywords: APP algorithm; A posteriori probability algorithm; Average bit error probability; Bandwidth; Channel codes; Concatenated convolutional codes; Error events; Interleaved continuous phase modulation; Iterative decoding; Minimum shift keying; Outer codes; Pseudorandom bit interleaver; Serially concatenated CPM; Serially concatenated continuous phase modulation; Simulations; System performance; Transfer function bound; Turbo codes; Upper bounds; Weight spectrum